Perceived Risk and Fear of Crime: Role of Social and Physical Incivilities - LaGrange, Randy L. (Journal of research in crime and delinquency, 1992)
The article examines the influence of a number of social and physical incivilities on two different reactions to crime. Prior research indicates that incivilities arouse fear of crime because they serve as signs of crime or as a prelude to trouble to neighborhood residents those things are not as they should be. Trash and liner lying around, abandoned buildings, vacant lots, unsupervised youth, people drunk in public, excess noise, and congestion may all invoke images of crime in the minds of citizens just as surely as do robberies, thefts, and assaults. The study found evidence of the incivility linkage; both social and physical incivility has significant zero-order correlations with fear of crime. However, the relationships are not strong, and they are considerably weaker than the relationships between social and physical incivility and perceptions of crime risk. In other words, although social and physical incivilities play a role in generating feelings of fear, the role is modest and almost entirely mediated through perceptions of crime risk